2020
DOI: 10.3389/fpsyg.2020.534428
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Quality of Life Trends in Early-Stage Lung Cancer Patients After Lobectomy

Abstract: Objective: Quality of Life (QoL) is an important predictor of patient's recovery and survival in lung cancer patients. The aim of the present study is to identify 1-year trends of lung cancer patients' QoL after robot-assisted or traditional lobectomy and investigate whether clinical (e.g., pre-surgery QoL, type of surgery, and perioperative complications) and sociodemographic variables (e.g., age) may predict these trends.Methods: An Italian sample of 176 lung cancer patients undergoing lobectomy completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…Many patients who overcame cancer find it difficult to go back to a new way of life, which can also impact their quality of life ( Götze et al, 2015 ). Patients’ quality of life is affected by specific factors related to the medical process, such as the specific treatment administered ( Marzorati et al, 2020 ), the location or type of cancer and the secondary effects derived from each treatment ( Gargantini and Martín Casari, 2019 ; Nilsen et al, 2021 ), as well as sociodemographic factors such as patients’ gender. Males tend to perceive higher quality of life than females ( Ayalon and Bachner, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many patients who overcame cancer find it difficult to go back to a new way of life, which can also impact their quality of life ( Götze et al, 2015 ). Patients’ quality of life is affected by specific factors related to the medical process, such as the specific treatment administered ( Marzorati et al, 2020 ), the location or type of cancer and the secondary effects derived from each treatment ( Gargantini and Martín Casari, 2019 ; Nilsen et al, 2021 ), as well as sociodemographic factors such as patients’ gender. Males tend to perceive higher quality of life than females ( Ayalon and Bachner, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 25 prospective studies met the inclusion criteria and were included in this study for analysis. 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Publication years ranged from 2003 to 2022. The PRISM decision tree is illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes the characteristics and outcomes for studies evaluating QOL after surgery alone. 13 , 14 , 20 , 23 , 29 , 30 , 31 , 33 , 35 All patients in the nine studies were diagnosed with having stage I or II NSCLC. The median number of patients was 173 and median age of patients was 67 years.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that patients experiencing severe adverse events during cancer treatment had a higher risk of treatment interruption, discontinuation, and death [32][33][34]. In addition, these toxicities can affect patients' quality of life and increase healthcare costs [35][36][37]. Therefore, managing toxicity is an important aspect of cancer treatment to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%